2010
DOI: 10.1007/s11661-010-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Strain Aging in New Generation Cr-Mo-V Steel for Reactor Pressure Vessel Applications

Abstract: A new generation nuclear reactor pressure vessel steel (CrMoV type) having compositional similarities with thick section 3Cr-Mo class of low alloy steels and adapted for nuclear applications was investigated for various manifestations of dynamic strain aging (DSA) using uniaxial tests. The steel investigated herein has undergone quenched and tempered treatment such that a tempered bainite microstructure with Cr-rich carbides was formed. The scope of the uniaxial experiments included tensile tests over a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The effect of force oscillation during low-cycle fatigue is visible across all applied deformation amplitudes. This material behaviour could be a manifestation of the dynamic strain ageing (DSA) occurrence in steel, [83] which may occur at room temperature in low-alloy, low-carbon steel following cold working, i.e. static strain ageing (SSA), or during plastic deformation, as is the case with the tested steel.…”
Section: B After Lcfmentioning
confidence: 99%
“…The effect of force oscillation during low-cycle fatigue is visible across all applied deformation amplitudes. This material behaviour could be a manifestation of the dynamic strain ageing (DSA) occurrence in steel, [83] which may occur at room temperature in low-alloy, low-carbon steel following cold working, i.e. static strain ageing (SSA), or during plastic deformation, as is the case with the tested steel.…”
Section: B After Lcfmentioning
confidence: 99%
“…This insight could be useful in understanding the impact of serrations on tensile and fracture properties in new generation low alloy steels that have been compositionally designed to suppress yield point phenomena. Previous studies by the authors in one such non-aging advanced low alloy steel [20,21] for reactor pressure vessel applications showed reduced influence of dynamic strain aging on tensile properties. In comparison with a martensitic stainless steel, which showed intense serrations and lowered fracture toughness [22], this advanced low alloy steel did not show systematic temperature-strain rate domain of appearance of serrations and lowering of ductility [20,21].…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies by the authors in one such non-aging advanced low alloy steel [20,21] for reactor pressure vessel applications showed reduced influence of dynamic strain aging on tensile properties. In comparison with a martensitic stainless steel, which showed intense serrations and lowered fracture toughness [22], this advanced low alloy steel did not show systematic temperature-strain rate domain of appearance of serrations and lowering of ductility [20,21]. Extending the influence of temporal metrics of serration obtained from an inhomogenous flow curve to the observations of lowered fracture properties due PLC phenomenon, the γ-parameter values promoting lower ductility and a rising ξ parameter could also reduce crack growth resistance by resulting in rapid fluctuations in crack tip plastic zone size [23].…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, the work hardening exponent and the occurrence of instability owing to DSA were studied in this research. Gupta et al [4] investigated the plastic deformation in a new generation of pressure vessel steels utilizing tensile testing in temperatures between 25°C and 600°C under low strain rates. It was found that the embrittling via DSA has been reduced owing to the concurrent occurrence of dynamic recovery as well as the influence of Mn/Ni atoms on mobility of interstitial atoms.…”
Section: Introductionmentioning
confidence: 99%